The root concept of leardership in the Qur'an : an exposition of its essence - Rahman, Ziaur (International Institute of Islamic Thought and Civilization (ISTAC), International Islamic University Malaysia, 2012)
This study focuses on the Western conventional concepts of leadership of Plato and Aristotle. The work also discusses several contemporary theories: traits, great-man, behavioural, situational/contingency, charismatic, visionary, transformational, leadermember exchange, ethical, strategic, authentic, cross-cultural and level 5 leadership, amongst others. It reveals that all concepts remain vulnerable and helpless when it comes to infusing the desired sense of accountability in the leader and hence, no central or foundation knowledge can be identified as the root concept. The work also looks at the concepts of Islamic scholars, namely AI-Mawardi, Al Ghazzali, Ibn Taiymiyyah, Ibn-Khaldun, Afzalur Rahman, Rafiq I Beekun and Jamal Badwi, and Naquib al-Attas, but no concept provides a single trait for becoming a successful leader. A survey on the holy Quran by thematic induction (al-Istiqrii al -Ma'nawi) clearly shows the existence of a pure trait Dhikrii al-Dar (Remembrance of the Hereafter), and a vast extent of this trait serves as the root concept of leadership. It reveals that Allah (swt) endowed this trait to Prophet Ibrahim (pbuh) and declared him the leader of mankind and asked Prophet Muhammad (pbuh) to follow Ibrahim (pbuh) as the best model. The introduction of this trait brings about universal vision, wisdom, a keen sense of accountability, motivation, courage and justice amongst other things. All these arguably made Muhammad (pbuh) the most influential leader of all times who was supremely successful in both the religious and secular level.